Effect of polyacrylic acid on dentin protease activities. Issue 8 (August 2015) - Ozcan, S.; Seseogullari-Dirihan, R.; Uctasli, M.; Tay, F.R.; Pashley, D.H.; Tezvergil-Mutluay, A.
Abstract Objective This study tested whether treatment of demineralized dentin with polyacrylic acid (PAA) has any activatory or inhibitory activity on dentin matrix metalloproteinases (MMP)s or cathepsin K (CAT-K). Methods Dentin beams (1 mm × 2 mm × 6 mm; n = 10) were completely demineralized with EDTA. After initial dry mass assessment, the beams were dipped into 37% phosphoric acid (PA), PA + 2% benzalkonium chloride (BAC), PA + 2% chlorhexidine digluconate (CHX), 10% PAA, PAA + BAC or PAA + CHX for 20 s. Demineralized beams without treatment served as control. All beams were incubated in simulated body fluid (SBF) for 1 week and the dry mass loss was evaluated. Aliquots of SBF were used to analyze solubilized telopeptide fragments using ICTP as indicator of MMP-mediated collagen degradation and CTX for CAT-K-mediated degradation. Additional demineralized beams (n = 10) were used to measure the influence of different chemical treatments on total MMP activity of EDTA-demineralized dentin using generic MMP assay. Data were analyzed by ANOVA (α = 0.05). Results Dry mass loss ranged from 6% (PA) to 2% for (PA-BAC) or (PAA-BAC) (p < 0.05). ICTP release of PAA-treated group was significantly higher (p < 0.05) than the control, and not significantly different from the PA group (p > 0.05). PA + CHX or PAA + CHX and PAA + BAC showed significantly lower ICTP than PA or PAA groups (p < 0.05). CAT-K activity increased significantly after 10% PAA treatment compared to control (p < 0.05) or to PA postreatment. Significance Demineralized dentin treated with 10% polyacrylic acid activated CAT-K more than 37% phosphoric acid; 2% chlorhexidine digluconate seems to be a better inhibitor of MMPs and CAT-K than 2% benzalkonium chloride.